Down syndrome: a risk factor for malocclusion severity? - Leandro Silva MARQUES; Carlos Eduardo Pinto ALCÂNTARA; Luciano José PEREIRA; Maria Letícia RAMOS-JORGE (Sociedade Brasileira de Pesquisa Odontológica, 2015)
The aims of the present study were to compare aspects related to malocclusion between individuals with Down syndrome (DS) and a control group, establish malocclusion severity, and identify determinant factors. A total of 120 individuals (60 with DS and 60 with no physical or mental impairment), were included in the study. Data were collected through interviews, analyses of the medical charts, and oral examinations. The criteria of the Dental Aesthetic Index were used for the diagnosis of malocclusion. Chi-square test (p ≤ 0.05) and multivariate logistic regression were used for comparisons between the two groups and to determine the association between the dependent (malocclusion severity) and independent variables. Statistically significant differences were found between the two groups for the following variables: missing teeth, diastema, overjet, mandibular protrusion, anterior open bite, posterior crossbite, facial type, lip incompetence, and Angle classification. DS, a history of premature birth, and long face pattern were found to be associated with malocclusion severity. Individuals with DS exhibited more occlusal problems than those in the control group.